Mechanical Behaviour of Tendinopathic Tendon: An Engineering Perspective - Hayes, Alex John Cullen (Curtin University, 2017)
Tendinopathy is a debilitating disease affecting millions of people worldwide. The aetiology of this disease is not well understood, and treatment remains difficult due to a lack of evidence-based management. This dissertation sought to quantify the mechanical behaviour of tendon in order to understand the difference between healthy and tendinopathic tendons. The findings in this dissertation offer insights that may contribute toward the development of better clinical management of tendinopathy.